WAME Editorial: Promoting Global Health: The World Association of Medical Editors Position on Editors’ Responsibility - Winker, Margaret A.; Ferris, Lorraine E.; Editors (WAME), and the World Association of Medical (Telehealth and Medicine Today, 2018)
No abstract available. Editor’s note: The World Association of Medical Editors (WAME) is a voluntary global organization of medical journal editors, who are uniquely positioned to define the critical role that editors have to play in promoting global health. In its 20 years of existence, WAME has sought to facilitate worldwide cooperation and communication among editors of peer-reviewed medical journals, improve editorial standards, and promote professionalism in medical journal editing. Medical journal editors have a social responsibility to promote global health by publishing, whenever possible, research that furthers health worldwide. What follows is a formal statement of the rational underlying and guiding that responsibility.